Tensor-based approach to the co-prime planar array signal processing - Wei RAO; Yufeng GUI; Dan LI (Tongxin xuebao)
For the co-prime planar array (CPPA) consisting of two sparse uniform rectangular array (URA),a new processing method based on tensor algebra was proposed to enhance the degrees of freedom (DoF).By dividing each URA into some overlapping subarrays,the received signals of two URAs were expressed as two tensors.And then the cross-correlation between such two tensors was processed into a received signal tensor of the virtual array.Analysis show that by the new method,the CPPA with 2 2L -1 physical elements can be transformed into a virtual sparse non-uniform planar array with (L+1) <mtext> </mtext>4 16 elements.For the virtual array,the tensor decomposition-based approach for estimating the two-dimensional (2-D) direction of arrival (DoA) of the incident signal is also proposed,which means 2-D spectral peak searching is avoided.Compared with the co-prime planar signal processing methods reported in the literature,the proposed method can increase the DoF from L 2to (L+1) <mtext> </mtext>4 16 +1 ,and has the better performance of the 2-D DoA estimation and lower computational complexity.Simulation results demonstrate the efficiency of the proposed method.